2022
DOI: 10.3390/ijerph19042119
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dietary Calcium Intake with Dental, Skeletal and Non-Skeletal Fluorosis among Women in the Ethiopian Rift Valley

Abstract: Fluorosis is a major public health problem in the Rift Valley of Ethiopia. Low calcium (Ca) intake may worsen fluorosis symptoms. We assessed the occurrence of fluorosis symptoms among women living in high-fluoride (F) communities in South Ethiopia and their associations with dietary Ca intake. Women (n = 270) from two villages provided clinical and questionnaire data. Dental fluorosis examination was done using Dean’s Index, and skeletal and non-skeletal fluorosis assessment was carried out using physical tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…This finding makes logical sense, as with increasing age, the individual has been exposed to high fluoride consumed in drinking water for a longer period of time and is in keeping with other studies. 20,22,28 Previous studies identify estrogen as a protective factor for SF, 11 with lower rates of SF seen in females. 11,24 This study found no significant difference between sexes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This finding makes logical sense, as with increasing age, the individual has been exposed to high fluoride consumed in drinking water for a longer period of time and is in keeping with other studies. 20,22,28 Previous studies identify estrogen as a protective factor for SF, 11 with lower rates of SF seen in females. 11,24 This study found no significant difference between sexes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that increased dietary calcium may mitigate the severity of SF, and it is important to consider promoting high-calcium foods or supplements that are cost-effective and sustainable, such as calcium-containing eggshell powder supplementation, which has been tested in Ethiopia. 22,28,34 A major advantage of this study is the large sample size. The reliability of the demographic data is strengthened by the comparison of results from the recent census within this established demographic surveillance site.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations